JUNK FOOD CONSUMPTION BEHAVIOR AND ITS IMPACT ON PHYSICAL AND MENTAL HEALTH AMONG ADOLESCENT GIRLS - Nobrihas, Maria Magdalena; Arlym, Lisa Trina; Widowati, Retno (International Journal of Multidisciplinary Research and Literature, 2025)
Junk food consumption in adolescents refers to the habit of consuming fast food or processed foods that are generally high in calories, saturated fat, sugar, and salt, but low in essential nutrients such as fiber, vitamins, and minerals. Junk food consumption harms nutritional status, as well as contributing to physical and mental health problems. In adolescent girls, excessive consumption of junk food can cause menstrual disorders. To analyze factors related to junk food consumption and the relationship between junk food consumption and its impact on nutritional status, physical health, mental health, and menstrual disorders. This study employed a cross-sectional design with a sample of 107 students from SMK Mutiara, using questionnaires and direct measurements for data collection. The data were analyzed using two approaches: bivariate analysis (Chi-Square test) and multivariate analysis (binary logistic regression). There was a relationship between peer factors, attitude, motivation, self-control, knowledge, taste, and social media exposure with junk food consumption, with a p-value of < 0.05. There was no significant relationship between junk food consumption and nutritional status, with a p-value of greater than 0.05. There is a relationship between junk food consumption and physical health, mental health, and menstrual disorders, with a p-value of < 0.05. The most significant factor influencing junk food consumption is exposure to social media. Young women need to increase awareness of the impact of excessive junk food consumption by managing peer influence, building healthy motivation, practicing self-control, and being more selective about food content on social media to maintain health.